Organizational learning as mediator of relationship between organizational culture, and innovativeness of higher education institution in Malaysia - Hafit, Nor Intan Adha; Asmuni, Azizan (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The survival of today’s higher education Institutions (HEI) depends on how these institutions adapt to change, improve practices and competitiveness. One important area these organizations need to pay attention to is organizational culture, which can create a supportive environment where innovation can flourish and competitiveness. Organizational learning also plays a vital factor in innovativeness in the organization. Therefore, the focus of this study is about the exploration of the role of organizational learning as mediator between the relationship of organizational culture and organizational innovativeness in Higher Education Institution (HEI) in Malaysia. A scientific research gap has been explored, through an intensive assessment of a previous study, in the literature on the relationship between organizational culture, organizational learning and organizational innovativeness. Subsequently, based on the dynamic capabilities theory, this study attempts to fill gap between constructs for competitive advantage. A conceptual framework has been proposed in this research study, as well as a contribution towards the enhancement of the related literature.